2023
DOI: 10.3389/frsen.2023.1106533
|View full text |Cite
|
Sign up to set email alerts
|

Gliders for passive acoustic monitoring of the oceanic environment

Abstract: Ocean gliders are quiet, buoyancy-driven, long-endurance, profiling autonomous platforms. Gliders therefore possess unique advantages as platforms for Passive Acoustic Monitoring (PAM) of the marine environment. In this paper, we review available glider platforms and passive acoustic monitoring systems, and explore current and potential uses of passive acoustic monitoring-equipped gliders for the study of physical oceanography, biology, ecology and for regulatory purposes. We evaluate limiting factors for pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Within this type of platforms, there are two main categories based on their buoyancy and locomotion system: ocean gliders and wave gliders. In the Mediterranean Sea, ocean gliders have been shown to be effective in detecting the presence of cetaceans and to be able to characterize their habitats [13]. Preliminary results presented in this study showed that also wave gliders can provide essential information about cetaceans in the Mediterranean Sea, especially in remote and offshore areas.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Within this type of platforms, there are two main categories based on their buoyancy and locomotion system: ocean gliders and wave gliders. In the Mediterranean Sea, ocean gliders have been shown to be effective in detecting the presence of cetaceans and to be able to characterize their habitats [13]. Preliminary results presented in this study showed that also wave gliders can provide essential information about cetaceans in the Mediterranean Sea, especially in remote and offshore areas.…”
Section: Discussionmentioning
confidence: 70%
“…More recently, autonomous observation systems (AOS) have been used for passive acoustic monitoring [5]. In particular, gliders can stay at sea for several months and are equipped with sensors to measure both environmental parameters and ambient noise [12][13][14]. Within this type of platforms, there are two main categories based on their buoyancy and locomotion system: ocean gliders and wave gliders.…”
Section: Discussionmentioning
confidence: 99%
“…The above studies [39][40][41][42][43][44][46][47][48], including our present study, highlight promising perspectives for cetacean population monitoring and reasonable price/energy cost acoustic transects [6,49]. However, precautions must be taken when trying to estimate population densities with a surface autonomous vehicle [38,50,51] as the usual assumption, that the animal's speed is slow compared with the vessel's speed, is violated. As such, this can introduce overestimation bias [52].…”
Section: Resultsmentioning
confidence: 78%
“…underwater Wi-Fi) (Figure 5, Duarte et al, 2021;Thomsen et al, 2021). In the future autonomous vehicles will replace ships in many ocean monitoring applications, which may contribute to reduce ambient noise because autonomous vehicles can operate substantially quieter than manned ships (Griffiths et al, 2001;Cauchy et al, 2023). In general, predictions should be taken as rough estimates because models cannot accurately quantify economic growths and they cannot predict adverse economic events such as wars, pandemics and economic crises.…”
Section: Discussionmentioning
confidence: 99%